INVESTIGATING THE SEMANTIC LOOPHOLES IN THE TRANSLATION OF “TERY ISHQ NACHAYAA “BY BABA BULLEH SHAH (Contemporary Journal of Social Science Review, 2025)
The process of translation is very complex. The paper explores the semantic loopholes and the sense of divine love from source text to target text during the Translation of “Tery Ishq Nachayaa” by KD. Duggal by implying the theory of Dr. Nicholson. The comparison between source text and target text has been analyzed to explore the cultural effects and sense of divine love also if the translated version is matched with sense of source text. The qualitative method has been used for this research. The findings conclude the gain of translation and elaborating the meaning with more intensity and providing literary elements used in poem effectively.